WORD SENSE DISAMBIGUATION: A ROADMAP - SRUTHI S.; B. KANNAN; BINU PAUL (Utilitas Mathematica, 2025)
Words that can be used with multiple senses are commonly referred to as polysemic words. Word Sense Disambiguation (WSD) is the process of finding the intended sense of a polysemic word in a given context. It is one of the most challenging problems in the area of natural language processing since it is an intermediate step in Machine Translation, Speech and Text processing, Information Retrieval and Extraction, etc. The research in this field has been ongoing for more than 60 years, and many changes can be seen in the techniques adopted. These changes are driven by the domain in which the WSD is applied and the availability of knowledge sources like corpora and machine-readable dictionaries. This paper aims to give a global perspective on the significant state-of-the-art techniques on Word Sense Disambiguation.